EVOLUSI DAN PERANAN SISTEM INFORMASI MANAJEMEN (SIM) DALAM ORGANISASI - Hasanah Noor, Farah; Annur, Saipul; Rosad, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of information technology has transformed Management Information Systems (MIS) from paper-based manual systems into integrated and sophisticated digital systems. This paper aims to analyze the evolution of MIS from the manual era, computerization, to the internet and digitalization era, as well as to explain its strategic role in modern organizations. This study employs a literature review approach by analyzing various primary and secondary sources related to the development and implementation of MIS. The analysis reveals that MIS has evolved significantly. In the manual era, MIS faced limitations such as human error, slow processes, and high operational costs. Entering the computerization era, MIS transformed into a faster and more accurate system through automation. In the current digital era, MIS is supported by technologies such as big data, cloud computing, the Internet of Things (IoT), and artificial intelligence (AI), enabling real-time information provision, supporting strategic decision-making, improving operational efficiency, and strengthening organizational competitiveness. In modern organizations, MIS serves as a strategic partner for management in the functions of planning, controlling, decision-making, and efficiency enhancement. However, MIS implementation still faces challenges such as investment costs, system integration, and human resource readiness. Therefore, organizations need to design adaptive and sustainable MIS development strategies.